Mechanism of Recovery from Acute Virus Infection. IX. Clearance of Lymphocytic Choriomeningitis (LCM) Virus from the Feet of Mice Undergoing LCM Virus-specific Delayed-type Hypersensitivity Reaction - Moskophidis, Demetrius; Fang, Lubin; Gossmann, Jan; Lehmann-Grube*, Fritz (Journal of General Virology, 1989)
SUMMARY As shown previously, after inoculation into the footpad of a mouse the lymphocytic choriomeningitis (LMC) virus multiplies locally. Beginning on day 6 or 7 after infection, the foot undergoes a delayed-type hypersensitivity (DTH) reaction which consists of two distinct phases that are mediated by CD8+ cells and CD4+ cells, respectively, and at about the same time the virus is eliminated. In general, for terminating infection of the mouse with LCM virus the CD8+ cytotoxic/suppressive T lymphocyte (CTL) is essential; we have now determined the cells that mediate control of the virus in a tissue undergoing a specific DTH reaction. Depletion, in infected mice, of all T lymphocytes by treatment with anti-Thy-1 monoclonal antibody prevented virus elimination from the foot, and the same was true when the CD8+ CTLs were removed. Depletion of the CD4+ helper/suppressor subset only marginally impaired the ability of the mice to rid themselves of the virus. The conclusion that here too the principal antiviral element is the CD8+ CTL was confirmed by experiments in which footpad-infected mice were adoptively immunized with virus-immune splenocytes from syngeneic mice selected for subclasses of T lymphocytes, or from mice differing in defined regions of the major histocompatibility complex (MHC), and also by experiments in which monocytes were virtually absent. However, CD8+ CTL alone or cells from MHC recombinant mice with identity in class I loci were never as antivirally active as unseparated splenocytes from syngeneic donor mice. Since the CD8+ cells’ performance could be optimized by interleukin-2, we assume that the CD4+ T lymphocytes function as accessory cells; the same probably applies to monocytes.
Keywords: LCMV